2014
DOI: 10.1002/art.38644
|View full text |Cite
|
Sign up to set email alerts
|

HLA–B27 Subtype Oligomerization and Intracellular Accumulation Patterns Correlate With Predisposition to Spondyloarthritis

Abstract: Objective. Mechanisms underlying the striking association of spondyloarthritis (SpA) with the class I major histocompatibility complex molecule HLA-B27 remain poorly understood. SpA-like disease develops spontaneously in B*2705-transgenic rats, in conjunction with high HLA-B27 expression levels. This study was undertaken to examine the effects of increased expression of HLA-B27 alleles that are differentially associated with SpA on oligomerization and intracellular redistribution.Methods. HeLa cells were trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…These substitutions affect the repertoire of bound peptides, biochemical and intracellular behaviors, and the conformational flexibility of the HLA-B27 heavy chain, and these features correlate with susceptibility to disease. [47][48][49] A recent study of single-nucleotide polymorphisms (SNPs) in the HLA region identified a small number of other statistically significant but weakly associated HLA class I and class II alleles (odds ratio for the alleles, 1.06 to 2.35). 50 The basis for the association between HLA-B27 and axial spondyloarthritis and ankylosing spondylitis remains unexplained.…”
Section: Role Of Hla-b27mentioning
confidence: 99%
“…These substitutions affect the repertoire of bound peptides, biochemical and intracellular behaviors, and the conformational flexibility of the HLA-B27 heavy chain, and these features correlate with susceptibility to disease. [47][48][49] A recent study of single-nucleotide polymorphisms (SNPs) in the HLA region identified a small number of other statistically significant but weakly associated HLA class I and class II alleles (odds ratio for the alleles, 1.06 to 2.35). 50 The basis for the association between HLA-B27 and axial spondyloarthritis and ankylosing spondylitis remains unexplained.…”
Section: Role Of Hla-b27mentioning
confidence: 99%
“…Moreover, the two structurally close but differently AS-predisposing B*2705 and B*2709 alleles have been shown to have similar intracellular trafficking and propensity to form oligomers [33]. However, more recently, it has been described a greater tendency of AS-associated B*2702, B*2705, B*2707 alleles to accumulate in 'dynamic' intracellular vesicles as misfolded/ aggregate proteins in comparison with the non-associated B*2706 allele [37]. This behaviour has been correlated with the B27 protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies by Jeanty et al showed increased oligomerization and intracellular accumulation of B*27:05 compared to B*27:06 when these heavy chains were transiently overexpressed in cells , which is precisely what one might predict if these 2 subtypes differ in their folding and/or unfolding properties. Of course, conformational flexibility could also be hypothesized to lead to autoreactivity.…”
mentioning
confidence: 88%